Potencial miogênico evocado vestibular no quadríceps femoral (thigh vemp): um novo ponto de captação - Souza, Maria Eduarda Di Cavalcanti Alves de (2018)
The Vestibular Evoked Myogenic Potential (VEMP) is a clinical test that evaluates the muscular response from high intensity auditory stimulation that can be used to evaluate vestibular function, specifically the saccule, inferior vestibular nerve, vestibular nucleus, vestibular-spinal tract and / or spinal accessory nerve. Considering that the number of research carried out within these potentials is increasing, the purpose of this thesis is to explain in detail the various stimuli and muscles used to perform the test, as well as the application of VEMP in clinical practice, and also propose a new point of capture of this potential, the quadríceps femoris, called thigh VEMP. Initially, a search for a theoretical reference was made, allowing a better understanding of the technique, its methodologies, and the demonstration of the various capture points already used (ocular VEMP - oVEMP, cervical VEMP - cVEMP, VEMP sural - leg VEMP and VEMP tríceps brachii - Sound Evoked Triceps Myogenic Potentials - SETMP'S) and its applications. Subsequently, the need to create a device capable of monitoring the muscle contraction of the muscle in question in order to perform the clinical test with efficiency was obtained, and due to the lacuna presented according to the technological prospection, a patent was developed characterized by capturing the stimuli electrical connections provided by the contracted muscle in order to make the performance and interpretation of audiological and vestibular tests more adequate. In view of the tests performed and results found, it is considered that, because it is a point of capture unheard of in the literature, some weaknesses were presented, on the other hand, it should be emphasized that due to its distance to the site of the sound stimulus received, a more complete observation of the spinal vestibule is possible, unlike the collection points already documented in the literature. Finally, the present study intends to arouse interest for this new point of capture as well as the use of it in new scenarios, in order to make it efficient in the daily practice clinical practice.